Proyek Pembangunan Jalan Masuk Di Pantai Koala - Martika, Aprilia; Utami, Pratiwi; Helen, Princes; Trimanda Yolanda, Silvi; Afdal Samsuddin, M. (BINER : Jurnal Ilmu Komputer, Teknik dan Multimedia, 2024)
The construction of the entrance road at Koala Beach aims to increase accessibility and support the development of natural tourism potential in this coastal area. This project involves planning, design and construction of roads taking into account technical, environmental and social aspects. This study discusses the stages of development which include location analysis, material selection, and the application of environmentally friendly construction technology. In addition, special attention is paid to environmental impacts, including mitigation efforts for coastal erosion and protection of coastal ecosystems. This research also evaluates the technical and topographic aspects required for constructing an access road. By considering many factors the optimal location for the construction of the driveway was identified. This study uses quantitative descriptive methods with secondary data collection and financial analysis involving parameters such as Net Present Value (NPV), Internal Rate of Return (IRR), Benefit Cost Ratio (BCR), and Payback Period (PP). The analysis results show that this project is financially feasible, with an NPV of IDR 1,277,944,618.73 (10% discount) and IDR 1,426,570,044.87 (15% discount), IRR of 12%, BCR of 2.04, and Payback Period 2.22 years. With a well-structured entrance, it is hoped that it can increase local tourism, open up new economic opportunities for the surrounding community, and strengthen the sustainability of natural resource management on Koala Beach. This research also offers recommendations regarding sustainability-based infrastructure planning for similar projects in other coastal areas.